Ty Cobb. - Alexander, Charles C. (Oxford University Press, USA, 1984)
Ty Cobb was one of the most famous baseball players who every lived. The author puts Cobb into the context of his times, describing the very different game on the field then, and successfully probes Cobb's complex personality.